WAYS OF IMPROVING THE NATIONAL CLASSIFICATION SYSTEM OF THE HOTEL INDUSTRY IN UZBEKISTAN (Marketing Journal, 2025)
This article conducted research to improve the national classification system for hotels and similar accommodation facilities in Uzbekistan, and also developed relevant proposals and recommendations. A number of necessary mechanisms are also proposed for i ntroducing a new item into the set of classification of hotels and similar accommodation facilities by category.
Keywords: tourism; hotel; accommodation facilities; accommodation services; classification; standard; criterion; personnel; client; differentiation of services; contact services; non -contact services; hospitality industry